2009
DOI: 10.1371/journal.pone.0006179
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role for Schizosaccharomyces pombe pik1 in Septation

Abstract: Background Schizosaccharomyces pombe pik1 encodes a phosphatidylinositol 4-kinase, reported to bind Cdc4, but not Cdc4G107S.Principal FindingsGene deletion revealed that pik1 is essential. In cells with pik1 deleted, ectopic expression of a loss-of-function allele, created by fusion to a temperature-sensitive dihydrofolate reductase, allowed normal cell proliferation at 25°C. At 36°C, cells arrested with abnormally thick, misplaced or supernumerary septa, indicating a defect late in septation. In addition to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 67 publications
(125 reference statements)
2
31
1
Order By: Relevance
“…Another hypothesis is that cdc4-s16 also compromises the function of some other Cdc4-binding partner that is part of a pathway that normally complements the pathway involving the septins. In this regard, it should be noted that there is good evidence that both S. pombe Cdc4 and its S. cerevisiae counterpart, Mlc1, interact with partners other than the type II myosin heavy chains and that these other partners are also important for cytokinesis (Stevens and Davis 1998;Boyne et al 2000;Shannon and Li 2000;Desautels et al 2001;D'Souza et al 2001;Motegi et al 2001;Win et al 2001;Lord and Pollard 2004;Luo et al 2004;Mulvihill et al 2006;Park et al 2009). The other partners include type V myosin heavy chains (S. pombe Myo51 and perhaps Myo52; S. cerevisiae Myo2), which are thought to be involved in the delivery of new plasma-membrane and cell-wall materials to the division site or (for Myo51) in some unknown function within the AMR; IQGAPs (S. pombe Rng2 and S. cerevisiae Iqg1), which may also be involved in plasma-membrane and cell-wall formation in addition to their roles in AMR function; and a phosphatidylinositol 4-kinase (S. pombe Pik1).…”
Section: Discussionmentioning
confidence: 99%
“…Another hypothesis is that cdc4-s16 also compromises the function of some other Cdc4-binding partner that is part of a pathway that normally complements the pathway involving the septins. In this regard, it should be noted that there is good evidence that both S. pombe Cdc4 and its S. cerevisiae counterpart, Mlc1, interact with partners other than the type II myosin heavy chains and that these other partners are also important for cytokinesis (Stevens and Davis 1998;Boyne et al 2000;Shannon and Li 2000;Desautels et al 2001;D'Souza et al 2001;Motegi et al 2001;Win et al 2001;Lord and Pollard 2004;Luo et al 2004;Mulvihill et al 2006;Park et al 2009). The other partners include type V myosin heavy chains (S. pombe Myo51 and perhaps Myo52; S. cerevisiae Myo2), which are thought to be involved in the delivery of new plasma-membrane and cell-wall materials to the division site or (for Myo51) in some unknown function within the AMR; IQGAPs (S. pombe Rng2 and S. cerevisiae Iqg1), which may also be involved in plasma-membrane and cell-wall formation in addition to their roles in AMR function; and a phosphatidylinositol 4-kinase (S. pombe Pik1).…”
Section: Discussionmentioning
confidence: 99%
“…8A). Previous studies showed that overexpression of wildtype Pik1p (but not mutant Pik1-R838Ap) inhibits cell growth (Park et al, 2009), indicating that light chain binding influences Pik1p function. We also saw growth inhibition when Pik1p was overexpressed from the medium-strength nmt1-41 promoter (Fig.…”
Section: Cam2p and Pik1p Function Together In The Cellmentioning
confidence: 97%
“…We employed a pik1-R838A mutant because this point mutation targets the IQ motif and abolishes Pik1p-Cdc4p (Park et al, 2009) and Pik1p-Cam2p (Fig. 7C) interactions without compromising the essential role of Pik1p in cell growth.…”
Section: Cam2p and Pik1p Function Together In The Cellmentioning
confidence: 99%
See 2 more Smart Citations